YKL-40 levels are associated with disease severity and prognosis of viral pneumonia, but not available in bacterial pneumonia in children - Xingge Yang; Guangyao Sheng (BMC, 2018)
Abstract Background Viral pneumonia is the main type of community-acquired pneumonia (CAP) in children. YKL-40, a chitinase-like protein, is regarded as a biomarker of the degree of inflammation. Methods Children who were diagnosed with CAP, including viral pneumonia, bacterial pneumonia, and dual infection, were included in the cohort study. The pathogenic diagnosis depended on PCR and immunoassay test. YKL-40 levels were examined twice by enzyme-linked immunoassay (ELISA). Results Serum YKL-40 levels were higher in patients with pneumonia than in healthy controls. The admission levels of YKL-40 in serum and Bronchoalveolar lavage (BALFs) indicated a positive correlation with the serum levels of C-reactive protein and other inflammatory cytokines (IL-6 and TNF-α). The disease severity have no correlation with the admission serum levels of YKL-40. Meanwhile, reductions in YKL-40 levels from initial admission levels to day 5 post-admission were correlated with disease severity. The multiple logistic analysis indicated the decreased extent of serum YKL-40 level as an independent prognostic predictor of severe cases in patients with viral pneumonia. Conclusions Reductions in serum YKL-40 levels on day 5 after receiving therapy is a possible prognostic biomarker for children with viral pneumonia.